PKM Pembuatan Rebricks-Paving Block dengan Memanfaatkan Limbah Sampah Plastik di SD Se-Gugus Ahmad Yani Demak - Aan Widiyono; Fivin Bagus Septiya Pambudi; Ariyanto; Ahmad Bagus Bambang Heri Hermawan; Heri Irawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Plastic waste is a significant problem not solved by elementary schools in the Ahmad Yani Cluster, Bonang District, Demak Regency. The problem is caused by ignorance and the inability to manage and process waste due to the large amount of plastic waste clogging the river. This Community Partnership Program (PKM) aims to empower teachers and students at Ahmad Yani Cluster Elementary Schools to utilize plastic waste by making eco-paving using the Rebricks-Paving Block Appropriate Technology (TTG) tool. The activities were carried out in several stages: socialization, training, technology application, assistance, and program evaluation. The activity results showed that this program positively impacted the partners, especially in increasing awareness and skills in plastic waste management. The program evaluation showed a high level of success, with 100% of respondents agreeing that plastic waste should be recycled and 90.50% rating the program as successful overall. In addition, 87.50% of partners felt helped in utilizing plastic waste with the TTG tool, and the implementation of the Rebricks-Paving Block TTG tool achieved excellent results with a score of 92.25%. The program successfully provides waste management solutions in the school environment. It can become a model for plastic waste management that can be widely applied.